The university in dissent : scholarship in the corporate university - Rolfe, Gary. (Society for Research into Higher Education (SRHE) series, 2013)
"The rise of corporatism in the North American University was charted by Bill Readings in the mid nineteen-nineties book The University in Ruins. The intervening years have seen the corporate university grow and extend to the point where its evolution into a large business corporation is seemingly complete. This book examines the factors contributing to the transformation of the university from a site of culture and knowledge to what might be termed an 'information factory', and explores strategies for how, in Readings' words, members of the academic community might continue to 'dwell in the ruins of the university' in a productive and authentic way. Drawing on the work of critics and philosophers such as, amongst others, Barthes, Derrida, Lyotard and Deleuze, The University in Dissent suggests that this can only be achieved subversively through the development of a community of philosophers who are prepared to challenge and critique the mission statement of the 'university of excellence' from within, focusing on how scholarly and academic writing will develop in this new era Summarising, contextualising and extending previous understandings of the rise of corporatism and the subsequent demise of the traditional aims and values of the university, Rolfe assesses the situation in contemporary UK and international settings. He recognises that change is at the core of current university education and explores some of the challenges and consequences of this shift in the academic world, showing how academics can work with, and against, change. This timely and thought provoking book is a must read for all academics at University level, as well as education policy makers"--